Utility of bronchoalveolar lavage for COVID-19: a perspective from the Dragon consortium - Tomassetti, Sara; Ciani, Luca; Luzzi, Valentina; Gori, Leonardo; Trigiani, Marco; Giuntoli, Leonardo; Lavorini, Federico; Poletti, Venerino; Ravaglia, Claudia; Torrego, Alfons; Maldonado, Fabien; Lentz, Robert; et al. (Frontiers in Medicine, 2024)
COVID-19 diagnosis can be challenging. BAL has shown to be feasible and useful in the diagnosis and management of both COVID-19 and its complications. This review summarises the evidences on the clinical and research utility of BAL in COVID-19 patients. Plain language summary: COVID-19 diagnosis and management can be challenging. BAL has shown to be feasible and useful in the diagnosis of COVID-19 and in the detection of coinfections, helping clinicians to guide appropriate treatment. Moreover, BAL is a potent research tool that is providing novel insights in the understanding of COVID-19 pathophysiology.Contributions to the study: all co-authors contributed to conception, design, draft and final revision of this manuscript.